VALIDITAS MODEL PEMBELAJARAN MATEMATIKA REALISTIK BERBASIS BUDAYA MANDAILING DALAM MEMBELAJARKAN KEMAMPUAN KONEKSI MATEMATIS SISWA - Ahmad, Marzuki (JURNAL EDUCATION AND DEVELOPMENT, 2018)
This study aims to produce products realistic mathematics learning model based on mandailing culture that meets validity for junior high school students. The learning model is the development of the Realistic Mathematics Education (RME) which is collaborated with the Mandailing culture, meaning that all the principles contained in the RME are applied in the model involving aspects of Mandailing culture in each component model and the component implementation of learning in the classroom. Research activities include developing models and supporting atmosphere of learning activities. Furthermore, to achieve the stated objectives, in this study four-D model development study was carried out with stages, namely the defining stage, planning phase, development stage and dissemination stage. The defining phase is carried out through an analysis of the Mandailing community culture to define and define social situations that can be applied to the learning system, then in learning activities an analysis of the objectives and boundaries of the material is analyzed. Furthermore, at the design stage aims to prepare prototypes of models and supporting atmosphere of learning activities. At the development stage validation is carried out. The dissemination phase is then carried out which is a socialization of learning models and tools that have been validated in junior high school teachers. Development research conducted provides acquisition of realistic mathematics learning models based on Mandailing culture in teaching mathematical connection skills and atmosphere support learning activities that meet validity and are well applied to junior high school students.